Morbidity pattern of underfives with moderate acute malnutrition in southern Nigeria - Udoh EE; Okorie O; Okpokowuruk FS; Udo E; Motilewa OO; Bassey V; Ikobah J; Adesina S; Ebunlomo I; Akpan M; Ekpo L; Uhegbu K; et al. (Ibom Medical Journal, 2024)
Background: Moderate acute malnutrition (MAM) is a leading cause of childhood morbidity and mortality globally. The morbidity pattern of underfives with this condition is yet to be described.